PENGARUH JEJARING BISNIS PEMIMPIN DAN JEJARING PEMIMPIN DENGAN PEMERINTAH, KEMAMPUAN MENYERAP PENGETAHUAN, DAN KEUNGGULAN KOMPETITIF UKMKM - Sulistiyowati, Firma; Bambang Harnoto, L.; Hans Kristian, Vincentius; Seto Wicaksono, Vincentius (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
This study aims to examine the influence of leaders' business networks and leaders' networks with the government in creating competitive advantage of Micro, Small and Medium Enterprises (MSMEs), moderated by Knowledge Absorption Ability. This research pays attention to the leader's individual attributes which are important factors and the leader's social network and its interaction with the leader's ability to absorb knowledge, taking the context in Indonesia, especially in Bantul district, Yogyakarta. This study uses a quantitative approach with a survey method, namely by distributing questionnaires. Respondents in this study were 88 owners of wooden batik or hand-written batik MSMEs in Bantul Regency, Yogyakarta Special Region (DIY). The sampling technique used was convenience sampling due to considerations of data availability and convenience for researchers. Partial Least Square (PLS) with Structural Equation Modeling (SEM) application is the data analysis technique used in this study. The results of this study show that leaders' business networks affect the competitive advantage of MSMEs in Bantul Regency. Meanwhile, leaders' network with the government has no effect on competitive advantage in Bantul. Leaders' ability to absorb knowledge does not significantly affect the relationship between leaders' business networks and MSME excellence. Likewise, the leader's ability to absorb knowledge weakens the relationship between the leader's business network and MSME excellence.